STATE OF THE IMMUNOLOGICAL FACTORS AND CYTOKINES AT THE PARTURIENT WOMEN WITH DISCOORDINATION AND EXCESSIVELY STRONG LABOR ACTIVITY - Kuzmina, O.A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The research of a state of the immunological factors and cytokines at the parturient women with discoordination and excessively strong labor activity is carried out. Is shown, that at (DLA) and (ESA)  there is a substantial growth of concentration cytokines and autoantibodies to the histic factor (FIII) in a periphery blood of the parturient women, the processes immune suppression, resulting in to an oppression T-cells of a link of immunodefence, augmentation of a level IgG, and drop of the contents IgM are broken.